Electronic Publications - Filipi Matutinović, Stela (Infotheca - Journal for Digital Humanities; Vol 5 No Special is (2004): Infotheca - Journal of Informatics and Librarianship, 2024)
On the World Library and Information Congress - 69th IFLA General Conference Section for Serial Publications & Reference Work held a workshop under the title: Electronic journals: how they are changing our lives.